2022
DOI: 10.3390/ijms23052768
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Potential Coding of Human Cytomegalovirus: New Predicted Transmembrane Proteome

Abstract: CMV is a major cause of morbidity and mortality in immunocompromised individuals that will benefit from the availability of a vaccine. Despite the efforts made during the last decade, no CMV vaccine is available. An ideal CMV vaccine should elicit a broad immune response against multiple viral antigens including proteins involved in virus-cell interaction and entry. However, the therapeutic use of neutralizing antibodies targeting glycoproteins involved in viral entry achieved only partial protection against i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 161 publications
(166 reference statements)
1
2
0
Order By: Relevance
“…The most significant targets included RL12, UL32 (Tegument protein pp150) and UL139. Protein structure predictions have suggested that UL139 is involved in cell adhesion and could be a good target for an anti-CMV vaccine 38 , supported by our results.…”
Section: The Anti-viral Antibody Repertoire Differs Strongly Between ...supporting
confidence: 86%
“…The most significant targets included RL12, UL32 (Tegument protein pp150) and UL139. Protein structure predictions have suggested that UL139 is involved in cell adhesion and could be a good target for an anti-CMV vaccine 38 , supported by our results.…”
Section: The Anti-viral Antibody Repertoire Differs Strongly Between ...supporting
confidence: 86%
“…3 The capsid surrounds and encloses the viral dsDNA genome (forming a nucleocapsid) and can be seen as an electron-dense structure in electron micrographs Protein core There are 39 core proteins, which are present in all strains and are highly conserved. 27 Among the core proteins, some are involved in cell entry and immunomodulation/immunoevasion; while the function of 17 of them (UL10, UL139 or US33A) has not been determined Enzymes Cytomegalovirus has an essential, maturational serine protease whose catalytic domain, assembling (28 kDa), is released by self-cleavage from a 74-kDa precursor (pPR, pUL80a) 28…”
Section: Capsomeresmentioning
confidence: 99%
“…The virus contains a double-stranded DNA genome of approximately 235 kbp, and it encodes numerous functional proteins, microRNAs, longnon coding RNAs and small peptides [3]. The HCMV genome contains >200 predicted open reading frames, with 71-77 proteins identified by mass spectrometry and in silico analysis [12][13][14]. Additionally, it also ex-presses four major non-coding RNAs (lncRNAs) along with at least 16 pre-miRNAs and 26 mature miRNAs [15].…”
Section: Introductionmentioning
confidence: 99%